Tingkat Pengetahuan Mahasiswa UPI Mengenai Informasi Polusi Cahaya di Kota Bandung - Rahmadiny, Aulia; Nurlaili, Dalfah; Zulfa, Haikal; Rahmawati , Rivani (DAS Institute, 2025)
This study aims to determine the level of knowledge among UPI students regarding information on light pollution. The research employs a descriptive survey method by distributing questionnaires to 26 respondents, namely students within the UPI campus environment. Based on the students' level of knowledge, it was found that their understanding of light pollution information falls into the